Analysis of The Income Statement in The Room Department of The Harper Perintis Makassar Hotel by Aston in 2020-2022 - Goeliling, Ardiansyah; Devi, Ni Nyoman (PT. Maju Malaqbi Makkarana, 2024)
This study aims to analyze the Income Statement of the Room Department at Harper Perintis Makassar By Aston Hotel in the 2020-2022 time span. The hospitality industry plays an important role in the tourism industry and the economy of a region. The existence of hotels not only provides a significant economic impact through income and employment for local communities, but also has a social impact by improving living standards and social conditions. The results of this study indicate that although Harper Perintis Makassar By Aston Hotel offers various additional facilities such as swimming pools, restaurants, massage services, and others, room types such as Superior Room and Deluxe Room continue to contribute significant departmental profits. However, there was a decrease in the Room Department's profit and loss at the end of 2017 due to room renovations and new facilities, as well as in 2019 due to the impact of the COVID-19 pandemic which resulted in a decrease in guest visits. This study uses quantitative research methods with a positivism approach. Primary data was obtained from the financial statements of the Rooms Department of Harper Perintis Makassar By Aston Hotel for 2020-2022. Data collection techniques involved field research with observation, direct interviews, and documentation.